Native Girl, Port of Spain - (:unkn) unknown (My University, 2009)
A young woman of East Indian origin carrying a basket of fruits on her head and one in her hand. The postcard is addressed to G.P. Stallinam of Rochester, New York and the sender is Raymond and Whitcomb Co. dated February 17th 1928. Affixed to the postcard is a one cent postage stamp.
Colour: Black and white; Style: Portrait; Other: Bordered; Undivided
Keywords: Postcards; Trinidad and Tobago; Women, East Indian--Trinidad and Tobago; Young women--Trinidad and Tobago; Ethnic costume--India; Clothing and dress--Trinidad and Tobago; Bracelets--India; East Indians--Trinidad and Tobago; Veils----Trinidad and Tobago; Baskets--Trinidad and Tobago; Manners and customs--Trinidad and Tobago; Transportation--Trinidad and Tobago; Pedestrian areas--Trinidad and Tobago